CONTEXT FOR DESIGNING A MA PROGRAMME IN NORWEGIAN LITERARY AND NON-LITERARY TRANSLATIONS AT BABEȘ-BOLYAI UNIVERSITY - TOMESCU BACIU, Sanda; POP, Raluca; DREVE, Roxana-Ema; RĂDUȚ, Raluca‐Daniela; ØVERLAND, Fartein Thorsen; MUREȘAN, Ioana-Andreea (Studia Universitatis Babeș-Bolyai Philologia, 2020)
Context for Designing a MA programme in Norwegian Literary and Non-Literary Translations at Babeș-Bolyai University. This study aims to explore the degree of motivation of current BA students and alumni as concerns their enrolment for a pilot MA-programme in Norwegian literary and non-literary translations at Babeș-Bolyai University (BBU). Details are provided regarding the context for designing such a unique master’s programme and the academic perspectives, as well as job opportunities that can be envisaged. A total of 147 respondents were included in this study and selected using convenience sampling. A structured questionnaire comprising open-ended and closed questions items was formulated in Romanian and sent online to respondents via Google forms. The study concludes that 95.2% of the respondents would be interested in enrolling for this pilot MA programme Norwegian literary and non-literary translations and thus, further consolidate their skills in Norwegian acquired during the BA programme in Norwegian language and literature. REZUMAT: Contextul dezvoltării unui program masteral în domeniul traducerilor ficționale şi non-ficționale, în limba norvegiană, la Universitatea Babeș-Bolyai. Acest studiu își propune să exploreze gradul de motivație al actualilor studenți și al absolvenților specializării Limbă și literatură norvegiană în ceea ce privește interesul pentru înscrierea acestora la un program pilot de master în domeniul traducerilor ficționale și nonficționale la Universitatea Babeș-Bolyai (UBB). Sunt oferite detalii cu privire la contextul proiectării unui astfel de program masteral și al perspectivelor academice, precum și al oportunităților de muncă ce pot fi avute în vedere. Un total de 147 de respondenți au fost incluși în acest studiu și au fost selectați utilizând eșantionarea de comoditate. Un chestionar structurat cuprinzând itemi cu întrebări deschise și închise a fost formulat în limba română și trimis online către respondenți prin intermediul aplicației formulare Google. Studiul concluzionează faptul că 95,2% dintre respondenți ar fi interesați să se înscrie la acest program masteral desfășurat în limba norvegiană în domeniul traducerilor ficționale și nonficționale. Acest demers va susține consolidarea competențelor lingvistice în limba norvegiană dobândite în timpul programului de licență – Limbă și literatura norvegiană. Cuvinte cheie: limba norvegiană, program masterat, traduceri ficționale, traduceri nonficționale, învățământ superior, Universitatea Babeș-Bolyai.